HIGHER EDUCATION AND ECONOMIC GROWTH A CASE STUDY OF PAKISTAN - Muhammad Tariq Mahmood, Sadaf Shaha (PJE, 2023)
This paper highlights the role of higher education for the economic growth in Pakistan. We explore the impact of increase in enrolment at tertiary level on the growth rate of income per worker. Estimating a growth model developed by Mankiv et. al. (1992), using the annual data of Pakistan, we find a robust relationship between higher education and economic growth in the long run. The model has also shown that investment in fixed capital has positive impact on economic uplift